The Effect of Massage Therapy on Aggression in Youth Wrestlers - Zadkhosh, Seyed Mohammad; Ariaee, Ehsan; Gharayagh Zandi, Hassan (Universitas Negeri Semarang, 2018)
For several reasons study of aggression is important. Unfortunately aggression can be found frequently among players and athletes and today is the main issue of competitions. Features and personality characteristics are the most important factors in aggressive behaviors and emotions. Although there are many studies about effects of massage on psychological factors but there are few studies in field of massage on athlete’s psychological factors especially in physical competitive sports such as wrestling. Therefore in this study, we examined the effects of sports massage on the level of aggression in adolescent wrestlers. In this study, sample population was selected out of 50 male adolescent wrestler. Aggression Questionnaire used to collecting wrestlers aggression data. At the beginning of each session, groups exercised wrestling training for 60 minutes and the experimental group received sports massage during 10 sessions for 25 minutes. The results showed that sports massage significantly reduces the level of wrestler’s aggression.